Hematologists’ perspective on advance directives, a French national cross-sectional survey – the ADORE-H study - K. Serey; A. Cambriel; Adrien Pollina-Bachellerie; Jacques-Olivier Bay; Carole Bouleuc; Laure Ladrat; Jean-Pierre Lotz; Francois Philippart (BMC Medical Ethics)
Abstract Background The onset of hematological malignancies can lead to acute and critical situations. It can also result in adverse outcome despite the significant advancements made in their therapeutic management. In this context, advance care planning and, in particular, advance directives (AD) play an essential role. However, the use of AD in patients with malignant hematological conditions remains very rare. Material & methods The aim was to evaluate the perception of AD by hematologists. We conducted a national online survey in France. All hematologist working in a hospital setting and treating malignant hemopathies were solicited. The questionnaire covered five areas: personal perception of AD; assistance in writing AD; patient information about AD; use of ADs; and demographic data. Results 318 hematologists (33.7% of the whole population), working in 103 different centers across France participated in the study. 72.6% (n = 231) of the respondents believed that AD could be beneficial for patient’s care. Only 32.7% talked about AD with their patients on a regular basis. The lack of utilization was correlated with the fear of creating anxiety for the patient (64.9%; n = 172) or for relatives (30.9%; n = 80), as well as the belief that AD were deemed inappropriate for their patients (57.8%; n = 145). 19.5% (n = 62) of responding hematologist offered their assistance to patients in writing AD. This proportion was higher in physicians who had previously worked in palliative care unit (35,6% vs. 16,8%, p = 0,0004). Conclusion The majority of the surveyed hematologist hold a positive opinion about AD. However, only a few discuss the matter with their patients. The fear of consequences for patients and relatives, particularly anxiety, remains the primary barrier to providing information about AD.